Personal health budgets - should patients be able to manage their care in a way that suits them? A concise narrative review. - Krzysztof Andrzej Tomaszewski (Jesuit University Ignatianum in Krakow, 2018)
RESEARCH OBJECTIVE: The aim of this concise review is to both demonstrate the pros and cons in regards to personal health budgets (PHBs), as well as critically evaluate their performance and possibilities. Another purpose of this paper is to familiarize the wider public with the concept of PHBs. THE RESEARCH PROBLEM AND METHODS: The reason behind introducing PHBs and direct payments was to bring social care and long-term healthcare "closer" to the patients in order to personalize treatment and support. By "personalization" we understand the possibility of choosing services that best meet the unique and individual needs of a specific person. However, the tempting concept of PHBs carries with itself both pros and cons. This qualitative, comprehensive narrative review brings to light the current state of knowledge and different parties' opinions on PHBs. THE PROCESS OF ARGUMENTATION: A PHB is an allocation of public/private financial resources used to identify and meet the health-related needs of a specific person. Such a resolution should potentially lead to new and innovative ways of spending the available funds, outside what traditional services offer, in order to personalize healthcare, increase its effectivity, and decrease the cost/benefit ratio. However, PHB's are not all-inclusive but cater to needs easily overlooked in the traditional healthcare system. RESEARCH RESULTS: The described PHB organization combines the best available clinical experience with the cumulated health- and care-related experience of the patients. This way both long-term and new short-term needs can be addressed and the intervention that has begun can last as long as the patient needs it. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: The healthcare system faces difficult times, and PHBs may be a potential solution to at least a part of the problems. The only question is will they be implemented correctly becoming a positive driver of change or will they become the anchor that pulls down a sinking ship?